2004
DOI: 10.1074/jbc.m408220200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Drosophila Larval Hemolymph Clot

Abstract: Components of the insect clot, an extremely rapid forming and critical part of insect immunity, are just beginning to be identified (1). Here we present a proteomic comparison of larval hemolymph before and after clotting to learn more about this process. This approach was supplemented by the identification of substrates for the enzyme transglutaminase, which plays a role in both vertebrate blood clotting (as factor XIIIa) and hemolymph coagulation in arthropods. Hemolymph proteins present in lower amounts aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
120
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 40 publications
9
120
0
Order By: Relevance
“…This precipitation leads to a soft clot, which is hardened through the activity of cross-linking enzymes. Recently, a proteomic study of Drosophila larval hemolymph before and after clotting has led to the isolation of several candidates for clotting factors, which include proteins with similarity to prophenoloxidase-activating proteases, two phenoloxidases, and substrates for the TGase (6). On the other hand, hemolectin, one of the most abundant hemolymph proteins in Drosophila, has been isolated and characterized as a coagulation-related factor (7).…”
mentioning
confidence: 99%
“…This precipitation leads to a soft clot, which is hardened through the activity of cross-linking enzymes. Recently, a proteomic study of Drosophila larval hemolymph before and after clotting has led to the isolation of several candidates for clotting factors, which include proteins with similarity to prophenoloxidase-activating proteases, two phenoloxidases, and substrates for the TGase (6). On the other hand, hemolectin, one of the most abundant hemolymph proteins in Drosophila, has been isolated and characterized as a coagulation-related factor (7).…”
mentioning
confidence: 99%
“…To date, the differences in catalytic activity and substrate specificity between dTG-A and -B have not been studied. A proteomic analysis of the Drosophila larval hemolymph clot showed the presence of TG substrate proteins and TG activity in the larval hemolymph, 6) and TG was found to act in hemolymph coagulation in Drosophila.…”
mentioning
confidence: 99%
“…A transcriptional profiling of distinct Drosophila blood cell (hemocytes) populations showed that, of the 13000 genes represented on the microarray, over 2500 exhibited significantly enriched transcription according to hemocytes subgroups; among these were genes encoding serine proteases and serpins such as Spn5 (Irving et al, 2005). Karlsson et al (Karlsson et al, 2004) and Irving et al (Irving et al, 2005) have detected of Spn5 in larval hemolymph, while De Gregorio et al, and Ligoxygakis et al, reported in flies deficient for another Serpin called Spn27A constitutive melanization of the cuticle and wings of adult flies, or melanotic tumors in larvae Ligoxygakis et al, 2002). In preliminary results, we failed to detect Spn5 mRNA in larval hemolymph cells, or aberrant activation of melanization in flies with a low basal level of Spn5 expression (data not shown).…”
Section: Discussionmentioning
confidence: 99%